HBR guide to thinking strategically. (Boston, Massachusetts: Harvard business review press, 2019)
Bring strategy into your daily work. As a manager, it's your responsibility to ensure that your work--and the work of your team--aligns with the overarching objectives of your organization. But when you're faced with competing projects and limited time, it's difficult to keep strategy front-of-mind. How do you think about the long term when the short term demands your attention? You need to change the way you think. The "HBR Guide to Thinking Strategically" provides practical tips and advice to help you see the big picture, so you can take that perspective into account in every aspect of your daily work--from making decisions to setting team priorities to attacking your own to-do list. You'll learn how to: understand your organization's strategy; align your team with key objectives; set and execute strategic priorities; spot trends in your company and in your industry; consider future outcomes when making decisions; manage trade-offs.--
Includes bibliographical references and index.
Keywords: Strategic planning; Business planning; Industrial management